Baseball Related Injuries: A Case Report on Acute Compartment Syndrome of the Forearm. (6th March 2022) - Pasque, Charles B.; Hendrix, Christopher
Abstract : Acute compartment syndrome is a difficult diagnosis to make due to its wide range of clinical presentations. Delay or misdiagnosis can cause devastating consequences such as Volkmann's ischemic contracture, permanent nerve damage, amputation, and death. Lower extremity compartment syndrome is more common than upper extremity compartment syndrome, with the forearm being the most common location for upper extremity compartment syndrome. Acute compartment syndrome is most caused by acute fracture trauma but can also be due to soft tissue crush injuries or vascular problems. We report a unique case of a male umpire being struck on the forearm by a baseball with subsequent progression to an acute compartment syndrome that required emergent fasciotomies. The patient made a full recovery with no known long-term sequelae.